Comparison of optic nerve head topography in normal eyes using confocal laser scanning tomograph and retinal thickness analyzer - Rekič, Andreja (Zdravniški vestnik, 2005)
Background. To compare optic nerve head topography measurements by Heidelberg retina tomograph I (HRT) and retinal thickness analyser (RTA) and thereby to determine clinical agreement between the devices. To investigate reproducibility of measurements for HRT and RTA. To obtain our own HRT and RTAdatabase for comparison of healthy and glaucomatous eyes. Methods. The study included 100 normal eyes of 50 white adults of both sexes (mean age of 55.5 (SD 9.5) years). Ophthalmologic examination, fundus phatography, HRT and RTA examinations were performed. To determine reproducibility 10 volunteers repeated the examination after a week. For HRT and RTA measurements mean (SD),median, 5th and 95th percentile, range and coefficient of variation were calculated. Differences in topographic parameters between HRT and RTA were tested for significance. Clinical agreement was assessed with "limits of agreement" and reproducibility expressed by repeatability coefficient and itraclass correlation coefficient (ICC). Results. Significant differences (p0.10 for RTA parameters cup area (0.15), rim area (0.19), maximum cup depth (0.13), height variation contour (0.11) and RNFL cross-sectional area (0.14). ICC was good (>90%) for all parameters, except for mean RNFL thickness (89%) for HRT and height variation contour (84%) for RTA. Conclusions. The two devices cannot be used interchangeably. (Abstract truncated at 2000 characters)
Keywords: Anatomy And Histology; diagnostika; glavkom; Microscopy, Confocal; Mikroskopija konfokalna; Mrežnica; očesne bolezni; oftalmologija; Optic Nerve; Retina; Vidni živec